Asperger syndrome and anxiety disorders (PAsSA) treatment trial: a study protocol of a pilot, multicentre, single-blind, randomised crossover trial of group cognitive behavioural therapy. Issue 7 (30th July 2013) - Langdon, Peter E; Murphy, Glynis H; Wilson, Edward; Shepstone, Lee; Fowler, David; Heavens, David; Malovic, Aida; Russell, Alexandra
Abstract : Introduction: A number of studies have established that children, adolescents and adults with Asperger syndrome (AS) and high functioning autism (HFA) have significant problems with anxiety. Cognitive behavioural therapy (CBT) is an effective treatment for anxiety in a variety of clinical populations. There is a growing interest in exploring the effectiveness of CBT for people with AS who have mental health problems, but currently there are no known clinical trials involving adults with AS or HFA. Studies with children who have AS have reported some success. The current study aims to examine whether modified group CBT for clinically significant anxiety in an AS population is likely to be efficacious. Methods and analysis: This study is a randomised, single-blind crossover trial. At least 36 individuals will be recruited and randomised into a treatment arm or a waiting-list control arm. During treatment, individuals will receive 3 sessions of individual CBT, followed by 21 sessions of group CBT. Primary outcome measures focus on anxiety. Secondary outcome measures focus on everyday social and psychiatric functioning, additional measures of anxiety and fear, depression, health-related quality of life and treatment cost. Assessments will be administered at pregroup and postgroup and at follow-up by researchers who are blinded to group allocation. The trial aims to find out whether or not psychological treatments for anxiety can be adapted and used to successfully treat the anxiety experienced by people with AS. Furthermore, we aim to determine whether this intervention represents good value for money. Ethics and dissemination: The trial received a favourable ethical opinion from a National Health Service (NHS) Research Ethics Committee. All participants provided written informed consent. Findings will be shared with all trial participants, and the general public, as well as the scientific community. Trial Registration: ISRCTN 30265294 (DOI: 10.1186/ISRCTN30265294 ), UKCRN 8370.